First necrophagy record for the genus Leiocephalus (Squamata: Leiocephalidae) in Cuba - Luis F. de Armas; Manuel Iturriaga (Novitates Caribaea)
In the backyard of an urban residence in San Antonio de los Baños, Artemisa Province, Cuba, an adult Leiocephalus c. carinatus Gray, 1827 was observed performing necrophagy over a two-week period. The lizard consumed domestic cockroaches (Periplaneta americana) and a ground beetle (Carabidae), both of which were fully dehydrated and had been dead for at least three weeks. This behavior is the first instance of necrophagy recorded in Cuba for a Leiocephalus species. Additionally, a list of all the recorded cases of necrophagy in this genus is provided.